Caenorhabditis elegans Predation on Bacillus anthracis: Decontamination of Spore Contaminated Soil with Germinants and Nematodes - Schelkle, Bettina; Choi, Young; Baillie, Leslie W.; Richter, William; Buyuk, Fatih; Celik, Elif; Wendling, Morgan; Sahin, Mitat; Gallagher, Theresa (Frontiers in Microbiology, 2018)
Remediation of Bacillus anthracis-contaminated soil is challenging and approaches to reduce overall spore levels in environmentally contaminated soil or after intentional release of the infectious disease agent in a safe, low-cost manner are needed. B. anthracis spores are highly resistant to biocides, but once germinated they become susceptible to traditional biocides or potentially even natural predators such as nematodes in the soil environment. Here, we describe a two-step approach to reducing B. anthracis spore load in soil during laboratory trials, whereby germinants and Caenorhabditis elegans nematodes are applied concurrently. While the application of germinants reduced B. anthracis spore load by up to four logs depending on soil type, the addition of nematodes achieved a further log reduction in spore count. These laboratory based results suggest that the combined use of nematodes and germinants could represent a promising approach for the remediation of B. anthracis spore contaminated soil.